Gender and Cassava (Manihot esculenta crantz) value chains: An intra-household gendered analysis of smallholder farmers in Tanzania - Thebe, Vusilizwe (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2018.